2003
DOI: 10.1148/radiol.2291021053
|View full text |Cite
|
Sign up to set email alerts
|

Osteoid Osteoma: Percutaneous Treatment with Radiofrequency Energy

Abstract: CT-guided percutaneous RF ablation of osteoid osteoma is a safe and effective technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
287
0
26

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(324 citation statements)
references
References 28 publications
11
287
0
26
Order By: Relevance
“…Image-guided percutaneous thermal ablation therapies are minimally invasive interventional techniques established in the local treatment of hepatic, renal, or osseous tumors [4][5][6][7][8][9][10][11][12]. Among these techniques, radiofrequency ablation (RFA) has now attained consideration for therapy of primary and secondary lung tumors [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Image-guided percutaneous thermal ablation therapies are minimally invasive interventional techniques established in the local treatment of hepatic, renal, or osseous tumors [4][5][6][7][8][9][10][11][12]. Among these techniques, radiofrequency ablation (RFA) has now attained consideration for therapy of primary and secondary lung tumors [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…RFA is the best described and most common thermoablative technique and has become established as the most effective method due to its high safety along with efficacy proven in numerous clinical studies [14]. As compared to conventional surgical methods, success and recurrence rates of CT-guided RFA is at least equivalent but with a lower complication rate, a shorter time of hospitalisation and faster reconvalescence [21,22]. Nevertheless, the usage of RFA in lesions close to neural structures-like in the spine-is limited due to the risk of adjacent neural tissue heating.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, several authors are sceptical regarding RFA for spinal osteoid osteomas because of the potential neurologic risks [9,12,14,19,21] and therefore open resection is still the treatment of choice for lesions of the occipitocervical junction [3]. Nevertheless, radiofrequency ablation of a spinal osteoid osteoma has been primarily reported in 1998 [18] and in recent years several authors reported their experience [6,7,12,14,21,23]. Animal models of RFA have shown that it may be performed safely in the vertebral body but the temperature of the surrounding soft tissue depends on the thickness of the cortical bone lamella [1,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positioning of the cauterization needle in the nidus of the OO was performed with a guided CT approach with a series of continuous scans of 1 mm and two-dimensional reconstructions [1,15,16]. Two dispersive cauterizations were utilized and usually placed cranial to the lesion in order to reduce the spread of radiofrequency towards the mobile structures [2].…”
Section: Methodsmentioning
confidence: 99%